2021
DOI: 10.1136/bmjopen-2021-050830
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after perioperative SARS-CoV-2 infection in patients with proximal femoral fractures: an international cohort study

Abstract: ObjectivesStudies have demonstrated high rates of mortality in people with proximal femoral fracture and SARS-CoV-2, but there is limited published data on the factors that influence mortality for clinicians to make informed treatment decisions. This study aims to report the 30-day mortality associated with perioperative infection of patients undergoing surgery for proximal femoral fractures and to examine the factors that influence mortality in a multivariate analysis.SettingProspective, international, multic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“… 13 , 14 , 15 , 16 , 17 , 18 , 19 This elevated risk of postoperative complications is also seen with postoperative acquisition of COVID-19 infection. 4 , 6 , 20 , 21 …”
Section: Clinical Riskmentioning
confidence: 99%
See 1 more Smart Citation
“… 13 , 14 , 15 , 16 , 17 , 18 , 19 This elevated risk of postoperative complications is also seen with postoperative acquisition of COVID-19 infection. 4 , 6 , 20 , 21 …”
Section: Clinical Riskmentioning
confidence: 99%
“…An additional research question is whether the type of anesthesia has a role in mitigating post-COVID-19 surgical patients’ perioperative risk. For example, one study showed no impact on mortality risk between regional or general anesthesia for patients with proximal femur fractures, 20 and case reports regarding the role of regional anesthesia are emerging. 66 Another area for future investigation is optimizing care for post-COVID-19 patients in an ambulatory (non-hospital) setting.…”
Section: Risk Mitigation and Risk Assessmentmentioning
confidence: 99%
“…Subsequent studies have demonstrated an elevated postoperative risk that persists for at least four weeks after the index infection, including increased mortality, pulmonary complications and venous thromboembolic events [5,[22][23][24][25][26][27]. This elevated risk of postoperative complications is also observed with the postoperative acquisition of SARS-CoV-2 infection [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Project Auditing COVID-19 in Trauma and Orthopaedics (IMPACT) Group found that, after adjusting for confounding factors, the risk of 30-day mortality for hip fracture patients with COVID-19 was three times greater than COVID-negative patients (COVIDSurg, 2021;Hall et al, 2020;Hall & Public Health Scotland, 2021). The multinational IMPACT-Global Hip Fracture Audit demonstrated that, in the context of COVID-19 infection, increased age, male sex, frailty, and pre-existing renal and pulmonary disease were associated with an increased 30-day mortality risk (Hall, Clement, IMPACT-Global, et al, 2022;Hall, Clement, MacLullich, Simpson, Johansen, et al, 2022;.…”
Section: Findings Of Previous Studies By the International Multicentrementioning
confidence: 99%